The value of open data government: a quality assessment approach (2021)
Data quality involves a set of characteristics, values, and expressions that are built iteratively. Open government data (OGD) shares the qualities of Big Data regarding volume, speed, accuracy, and value, and the purpose of achieving stakeholders’ reuse stands out. This study uses a bibliographic review to identify the relationships among big data, open data, data quality, and value. We conclude that OGD, a recent trend, encourages collaboration and citizen participation and enables reusing data to pursue public and private innovation. Ensuring data quality makes it possible to obtain value from its reuse and generate Economic Value, Commercial Value, Social Value, and Public Value. Consumers require a solid basis of trust before using public information, which requires a data quality assurance process that strengthens and intensifies the inherent value of the data and activates its potential in different contexts.